Analisis Pengukuran Kualitas Aplikasi E-Guestbook Menggunakan Metode Six Sigma pada Kejaksaan Tinggi Sumatera Selatan - Rizky, Rizky Priatama; Tata Sutabari, Tata Sutabari (Router : Jurnal Teknik Informatika dan Terapan, 2025)
The e-guestbook application is an application used to record and process guest data arriving at an institution. The quality of the e-guestbook application system needs to be measured to determine the level of quality and user satisfaction with the application. This study aims to analyze the quality measurement of the e-guestbook application using the Six Sigma method at the South Sumatra High Prosecutor's Office. The Six Sigma method was chosen because it can identify and measure Critical to Quality (CTQ), thereby improving the quality of the application. The research results show that the sigma value of the e-guestbook application is 4.16, which means the quality of the application is very good. However, there are several aspects that need improvement, namely the ease of use of the application, the accuracy of the information, and the availability of application features. The recommended improvements are enhancing the user interface, validating input data, and adding a report printing feature. The application of the Six Sigma method has proven effective in measuring and improving the quality of the e-guestbook application at the High Prosecutor's Office of South Sumatra